Pengaruh Rasio Keuangan terhadap Pertumbuhan Laba: Studi Kasus Perusahaan subsektor Otomotif dan Elektronika - Dewi Agustina (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to analyze the effects of Quick ratio, Debt to Equity ratio, Net Profit Margin ratio, Return on Equity ratio, Return on Investment ratio, Current Ratio, to Profit Growth in electronic sub sector and automotive sub sector and components listed on the Indonesian Stock Exchange for the period 2019-2022. This study used secondary data obtained from the website official www.idx.co.id. The results of this study show that the variable Quick Ratio and Debt to Equity Ratio have a significant effect on profit growth. Meanwhile, Current Ratio, Net Profit Margin Ratio, Return on Equity Ratio, Return on Investment Ratio have insignificant effect on profit growth.